PoliDB : a repository for storing multi-dimensional relation information case study with Indian politics - Toh, Jeck Chee (2014)
Nowadays, there has been a proliferation of social network usage. Social networks not only enhance relationships among people by providing a more convenient form of communication (Petre, 2010), but also contain a large amount of information. Patterns or trends can be analysed with a system that has the capability of capturing, processing, storing and analysing data from social networks. Twitter is one of the social platforms that is commonly used to express small thoughts, feelings or opinions in words. It is largely used by people all around the world to express their thoughts and also as an advertising tool by celebrities. A text message broadcast through Twitter is called a tweet. Each tweet can contain a maximum of 140 characters. The message size restriction keeps things scan-friendly which is suitable for the modern, attention-deficit world (Gil, 2012). Hence, tweet data is used in the project as a major input for the analysis of the Indian political trend. As the India general election in 2014 approaches, discussions about the Indian politics becomes more popular on social platforms. This has created an opportunity for obtaining a huge amount of related information for analysing the Indian politics.